1987
DOI: 10.1073/pnas.84.21.7595
|View full text |Cite
|
Sign up to set email alerts
|

Atypical mitochondrial DNA from the deep-sea scallop Placopecten magellanicus

Abstract: The mitochondrial DNA of most metazoan animals is highly conserved in size, averaging about 17 kilobase pairs (kbp). The mitochondrial DNA from the deep-sea scallop Placopecten magellanicus, in contrast, has been found to be approximately 34 kbp long. It is also highly variable in size from individual to individual and is unusual in the extent of its size variation. Mitochondrial DNAs from individuals collected at the same site differ by as much as 7 kbp. The size variation is due largely to differences in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(30 citation statements)
references
References 25 publications
0
29
0
1
Order By: Relevance
“…The mtDNA recombination observed in triploid crucian carp seemed to be different from other mtDNA recombination found in the nematode M. javanica (Lunt and Hyman 1997) and various other animal species (Solignac et al 1986;Snyder et al 1987;Rand and Harrison 1989;Buroker et al 1990;Ludwig et al 2000). The latter type of mtDNA recombination was mediated by a mechanism of unequal crossing over that resulted in products of unequal lengths of mtDNA.…”
Section: Discussionmentioning
confidence: 82%
“…The mtDNA recombination observed in triploid crucian carp seemed to be different from other mtDNA recombination found in the nematode M. javanica (Lunt and Hyman 1997) and various other animal species (Solignac et al 1986;Snyder et al 1987;Rand and Harrison 1989;Buroker et al 1990;Ludwig et al 2000). The latter type of mtDNA recombination was mediated by a mechanism of unequal crossing over that resulted in products of unequal lengths of mtDNA.…”
Section: Discussionmentioning
confidence: 82%
“…The additional Hpa II fragments seen in the two mtDNA lanes map elsewhere in the genome (20). (b and c) mtDNA from the three sisters H709, H512, and H576 ( to humans (16,(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39). In all those cases examined at a detailed level, a repeated sequence element was involved.…”
Section: Resultsmentioning
confidence: 99%
“…Two fragments of mtDNA, which showed no evidence of length variation after restriction digest screening of a number of individuals, were chosen for sequencing; a 2 kb EcoRl-Hindlil fragment and a 3.85 kb HindIII-HindIII fragment. MtDNA for ligation was purified as above from a single animal except that two bouts of sucrose gradient centrifugation (Snyder et al, 1987) were used to ensure complete separation of mitochondria from nuclei. Restriction enzyme-treated mtDNA was ligated into pBluescript KS (Stratagene) using standard protocols (Sambrook et a!., 1989) and used to transform competent XL1-blue E. coli.…”
Section: Samplingmentioning
confidence: 99%
“…The marker of choice for the majority of population level comparisons has been the mitochondrial DNA (mtDNA), and restriction fragment length polymorphism (RFLP) analysis of the mtDNA molecule has been widely applied to marine species (Ovenden, 1990). However, recent work has shown that in many scallops (Snyder et a!., 1987;Gjetvaj et al, 1992;Repin & Brykov, 1992;Boulding et al, 1993), including P maximus (Rigaa et al, 1993), mtDNA length differences between individuals and species are extensive. Pecten maximus mtDNA is variable in length as a result of varying numbers of a tandemly repeated 1.55 kb element (Rigaa et al, 1993(Rigaa et al, , 1995.…”
Section: Introductionmentioning
confidence: 99%